2012
DOI: 10.1080/13574809.2012.666208
|View full text |Cite
|
Sign up to set email alerts
|

From Urban Concept to Urban Engineering: The Contribution of Distributed Collaborative Design to the Management of Urban Projects

Abstract: The complexity of urban systems is an increasingly common topic in academic literature. Following in the footsteps of the industrial sector, which has understood this issue for many years now, urban engineering must also tackle the challenges created by complex systems. Industrial engineering has provided a number of responses to this challenge, including design technologies, which are notably collaborative. It seems possible, at least in theory, to transfer a number of best practice methods and adapt these to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Our study case, observed during a lon embraces a large variety of involvements o the co-design process of the urban pr neighborhood project in Living Lab mode i operational contributions on mobility shown, usage to experimentation of co-created solutio Some methods and postures from indus are adapted and shared with actors of the lo the logic of distributed collaborative design project [8], a technological transfer is engag modifications are proposed. In this way, an a for participatory process (tools, methods, governance (stakeholders management) is urban design, Living Lab Mode seemed to these new abilities to include users throu project.…”
Section: E a Methodology Stemming From The Usementioning
confidence: 99%
See 3 more Smart Citations
“…Our study case, observed during a lon embraces a large variety of involvements o the co-design process of the urban pr neighborhood project in Living Lab mode i operational contributions on mobility shown, usage to experimentation of co-created solutio Some methods and postures from indus are adapted and shared with actors of the lo the logic of distributed collaborative design project [8], a technological transfer is engag modifications are proposed. In this way, an a for participatory process (tools, methods, governance (stakeholders management) is urban design, Living Lab Mode seemed to these new abilities to include users throu project.…”
Section: E a Methodology Stemming From The Usementioning
confidence: 99%
“…Reference [8] shows that in urban project management in developed countries, it is more and more admitted that make professionals of urban issues collaborate and understand endusages of an urban project allow to take better strategic decisions (particularly in sustainable and economic perspectives). Despite that, during the initial stage of the design process, the citizen participation remains weak.…”
Section: A From Industrial Design To Urban Co-designmentioning
confidence: 99%
See 2 more Smart Citations
“…In an industrial setting, concepts are the first collaborative products at the early stages of design. Concepts enable an improved formulation of the meaning, planning, and program of a project [25]. Based on concepts, models are executed as a representation of a system using general rules.…”
Section: Phases Of Urban Process: From Concept To Model Experimentatmentioning
confidence: 99%